2018
DOI: 10.1117/1.jbo.23.9.091402
|View full text |Cite
|
Sign up to set email alerts
|

Caries detection and quantification around stained pits and fissures in occlusal tooth surfaces with fluorescence

Abstract: Occlusal discoloration due to staining frequently occurs on the pits and fissures of teeth. Noncariogenic discoloration (non-CD) refers to the attachment of staining chromogens to sound surfaces, whereas cariogenic discoloration (CD) represents the discoloration of porous structures due to bacterial metabolites and mineral loss from the enamel surface. This study evaluated whether it is possible to distinguish between non-CD and CD on stained occlusal surfaces with fluorescence assessed by the quantitative lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Previous studies using the QLF technique mainly focused on red fluorescence for mature and pathogenic plaques 21 , 22 . However, Lee et al first reported, through an in vitro experiment, that the red fluorescence observed in mature pathogenic plaques is also present in occlusal carious lesions 23 . Demineralized early enamel carious lesions contain fewer minerals and higher amounts of organic matter and water than healthy enamel 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using the QLF technique mainly focused on red fluorescence for mature and pathogenic plaques 21 , 22 . However, Lee et al first reported, through an in vitro experiment, that the red fluorescence observed in mature pathogenic plaques is also present in occlusal carious lesions 23 . Demineralized early enamel carious lesions contain fewer minerals and higher amounts of organic matter and water than healthy enamel 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that porphyrin derivatives are mainly used as uorescent dyes for caries lesion assessment with laser uorescence (LF) 36,37,38,39,40 . However, the porphyrin derivatives are not suitable as a uorescent dye for DEQLF, since they already exist in natural caries lesions as bacterial metabolites 20,41,42,43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…In dentistry, there have been efforts to objectively and quantitatively evaluate caries lesions using optical technologies. Among them, quantitative light-induced uorescence (QLF) technology uses blue visible light of 405 nm to detect oral diseases (e.g., dental caries, dental abrasion, tooth ssure, and pathogenic dental plaque) 16,17,18,19,20,21,22,23 . When an early caries lesion is irradiated with blue visible light, it emits a relatively dark auto uorescence compared to sound enamel due to light scattering by the porous structure of the surface layer 24,25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…The high rate of class I cavities involved in this study should be considered since the higher caries risk in adults and adolescents is on proximal surfaces. This aspect can be related to the equivocated diagnosis of occlusal caries [30]. Occlusal discoloration as a diagnostic criterion could lead to a false-positive caries diagnosis and, consequently, the premature indication of restorative procedures, assuming that placing a restoration "fixes" dental caries, which is not true [31].…”
Section: Discussionmentioning
confidence: 99%